Hydraulic Considerations for Citrus Microirrigation Systems - Brian Boman; Sanjay Shukla (EDIS)
Hydraulics is the study of the behavior of liquids as they move through channels or pipes. Hydraulic principles govern the flow of water through irrigation pipes. A basic understanding of these principles is necessary for understanding the design and operation of irrigation systems. This publication provides an introduction to hydraulics as it relates to citrus microirrigation. This document is Circular 1425, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: May 2004.